Load transfer behaviour of bored piles in old alluvium formation [electronic resource] - 274413 Liknaswaran Kobarajah (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2007